Comprehensive Chlorine Suppression: Advances in Materials and System Technologies for Direct Seawater Electrolysis - Cenkai Zhao; Zheyuan Ding; Kunye Zhang; Ziting Du; Haiqiu Fang; Ling Chen; Hao Jiang; Min Wang; Mingbo Wu (Nano-Micro Letters)
Highlights Rational design of chlorine-suppressing catalysts based on mechanistic insights. Overview of recent advances in cutting-edge seawater electrolysis systems. Discussion of challenges and potential directions for direct seawater electrolysis enhancement.